2021
DOI: 10.1016/j.celrep.2020.108626
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic Shifts in the Composition of Resident and Recruited Macrophages Influence Tissue Remodeling in NASH

Abstract: SUMMARY Macrophage-mediated inflammation is critical in the pathogenesis of non-alcoholic steatohepatitis (NASH). Here, we describe that, with high-fat, high-sucrose-diet feeding, mature TIM4 pos Kupffer cells (KCs) decrease in number, while monocyte-derived Tim4 neg macrophages accumulate. In concert, monocyte-derived infiltrating macrophages enter the liver and consist of a transitional subset that expresses Cx3cr1/Ccr2 and a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
244
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(313 citation statements)
references
References 55 publications
(71 reference statements)
24
244
1
Order By: Relevance
“…(B) If the inflammatory insult is not resolved (e.g., in case of chronic infection, repeated injury or metabolic stress associated with increased lipid burden), the resolution phase is not reached and chronic inflammation develops. Increased KC death activates the niche cells (LSECs, HSCs and hepatocytes) to call in Ly6C hi monocytes to replenish lost KCs (4,(23)(24)(25)32). Continuous activation and/or tissue injury may lead to death of structural cells of the liver.…”
Section: Acute Plasticity Of Resident Kcsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) If the inflammatory insult is not resolved (e.g., in case of chronic infection, repeated injury or metabolic stress associated with increased lipid burden), the resolution phase is not reached and chronic inflammation develops. Increased KC death activates the niche cells (LSECs, HSCs and hepatocytes) to call in Ly6C hi monocytes to replenish lost KCs (4,(23)(24)(25)32). Continuous activation and/or tissue injury may lead to death of structural cells of the liver.…”
Section: Acute Plasticity Of Resident Kcsmentioning
confidence: 99%
“…In certain inflammatory settings, such as NASH and fibrosis/cirrhosis, it has recently been shown that these cells express genes including Spp1, Gpnmb (mouse) Trem2 and Cd9 (mouse and human). In mouse, these cells were termed lipid-associated macrophages (LAMs) while in human they were called scar-associated macrophages (SAMs) ( 4 , 30 , 32 ). Alignment of the LAMs and SAMs showed significant overlap ( 4 ) suggesting these could indeed be equivalent populations.…”
Section: Hepatic Macrophage Populationsmentioning
confidence: 99%
“…This is best exemplified by recent studies of Kupffer cells in mouse models of metabolicassociated fatty liver disease (MAFLD). Intriguingly, Kupffer cell numbers and/or identity is lost during the course of the MAFLD sequelae non-alcoholic steatohepatitis (NASH) (62,150,161,162). These cells are, at least in part, replaced by monocytederived macrophages that appear to seed the liver long-term and assume transcriptional programs similar to those of their longterm TRM counterparts.…”
Section: Metabolism Of Homeostatic and Pro-resolving Tissue-resident Macrophagesmentioning
confidence: 99%
“…These cells are, at least in part, replaced by monocytederived macrophages that appear to seed the liver long-term and assume transcriptional programs similar to those of their longterm TRM counterparts. This is intriguing because these newcomers, despite exhibiting transcriptional, epigenetic, and functional similarities to their long-lived Kupffer cell counterparts (34,150,161), appear to have different responses to lipids (including triglycerides) and contribute to NASH progression differently (161,162). For instance, on one hand, monocyte-derived liver TRMs appear to less efficiently promote storage of triglycerides and exacerbate liver fibrosis (161).…”
Section: Metabolism Of Homeostatic and Pro-resolving Tissue-resident Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation